2022
DOI: 10.1111/jace.18620
|View full text |Cite
|
Sign up to set email alerts
|

Ablation behavior of (Hf–Ta–Zr–Nb–Ti)C high‐entropy carbide and (Hf–Ta–Zr–Nb–Ti)C–xSiC composites

Abstract: The ablation behavior of (Hf-Ta-Zr-Nb-Ti)C high-entropy carbide (HEC-0) was investigated using a plasma flame in air for different times (60, 90, and 120 s) at about 2100 • C. The effect of SiC content on the ablation resistance of HEC-xSiC composites (x = 10 and 20 vol%) was also studied. The linear ablation rate of HEC-0 decreases with increasing ablation time, showing the positive role of the oxide layer with a complex composition. The linear ablation rate of HEC-10 vol% SiC (0.3 µm s −1 ) is only a 10th of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The results indicated that enhanced ablation resistance was ascribed to the formation of ZrxTiyC solid solution and amorphous SiC, then a Zr-Ti-Si-O glassy phase with high viscosity and low evaporation pressure was acquired during the ablation process. Wang et al [21] studied the ablation resistance of (Hf-Ta-Zr-Nb-Ti)C-xSiC composites. The results shown that (Hf-Ta-Zr-Nb-Ti)C-10 vol% SiC has a linear ablation rate of 0.3 μm/s, which is only one-tenth of that of (Hf-Ta-Zr-Nb-Ti)C. The significant improvement is probably resulting from the oxide layer with molten SiO2 and Hf-Zr-Si-O oxides.…”
Section: J U S T a C C E P T E Dmentioning
confidence: 99%
“…The results indicated that enhanced ablation resistance was ascribed to the formation of ZrxTiyC solid solution and amorphous SiC, then a Zr-Ti-Si-O glassy phase with high viscosity and low evaporation pressure was acquired during the ablation process. Wang et al [21] studied the ablation resistance of (Hf-Ta-Zr-Nb-Ti)C-xSiC composites. The results shown that (Hf-Ta-Zr-Nb-Ti)C-10 vol% SiC has a linear ablation rate of 0.3 μm/s, which is only one-tenth of that of (Hf-Ta-Zr-Nb-Ti)C. The significant improvement is probably resulting from the oxide layer with molten SiO2 and Hf-Zr-Si-O oxides.…”
Section: J U S T a C C E P T E Dmentioning
confidence: 99%